Determinan Penerimaan Pajak Daerah dan Pengaruhnya terhadap Pertumbuhan Ekonomi di Kota Jambi - Nella Ervina; Syamsurijal Tan; Erni Achmad (Universitas Batanghari, 2023)
This study aims to: (1) analyze the development of local taxes in Jambi City in the period 1998–2021. (2) To analyze what factors affect local tax revenue in Jambi City in the period 1998–2021. (3) To analyze the effect of local tax revenue on economic growth in Jambi City in the period 1998–2021. This study uses secondary data in the form of time series data during the period 1998–2021. The analysis techniques used in this research are descriptive, qualitative, and quantitative. The model used in this analysis is an econometric model with the Ordinary Least Squares (OLS) model. The results of the study provide conclusions. (1) The development of tax revenue in Jambi City in 1998–2021 tends to experience fluctuations, but overall tax revenue in Jambi City has shown quite good development. (2) GRDP, population, and investment partially affect the amount of hotel tax revenue in Jambi City. Meanwhile, inflation and government policy variables have no significant effect on the amount of hotel tax revenue in Jambi City. Furthermore, GRDP, population, inflation, and investment partially affect the amount of restaurant tax revenue in Jambi City. Meanwhile, the government policy variable has no significant effect on the amount of restaurant tax revenue in Jambi City. Next, GRDP, population, investment, and government policy partially affect the amount of entertainment tax revenue in Jambi City. While the inflation variable has no significant effect on the amount of entertainment tax revenue in Jambi City, GRDP, inflation, investment, and government policy partially affect the amount of billboard tax revenue in Jambi City. Meanwhile, the population variable has no significant effect on the amount of billboard tax revenue in Jambi City. Finally, GRDP, inflation, investment, and population partially affect the amount of street lighting tax revenue in Jambi City. Meanwhile, the government policy variable has no significant effect on the amount of street lighting tax revenue in Jambi City. (3) Entertainment, hotel, and restaurant taxes positively and significantly affect economic growth in Jambi City from 1998–2021. Meanwhile, billboard taxes and street lighting taxes have no significant effect on economic growth in Jambi City.